2013
DOI: 10.1111/1467-9248.12063
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence, Political Engagement and Context

Abstract: Scholars of American politics have generally found a negative relationship between ambivalence and political engagement. This study explores such conclusions and argues that the effect of ambivalence on engagement varies according to electoral context. Using a multi‐level modeling strategy, I find that ambivalence has a significant overall effect on political engagement for citizens in the United States but a lesser overall impact for citizens in Great Britain. Yet by allowing the slope and the intercept of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
0
21
1
Order By: Relevance
“…3 The formula can be applied to different types of measures. It has been applied to information on (1) the number of positive and negative evaluations of parties (Bassinger and Lavine, 2005; Lavine, 2001; Lavine et al, 2012; Yoo, 2010), on (2) data from Likert scale responses of two parties (Rudolph, 2011) or on (3) feeling thermometer scores of two different parties (Johnson, 2014; Leiter, 2019; Mutz, 2002). I follow the latter approach and make use of citizens’ evaluations of parties to capture ambivalence.…”
Section: Data and Operationalizationmentioning
confidence: 99%
“…3 The formula can be applied to different types of measures. It has been applied to information on (1) the number of positive and negative evaluations of parties (Bassinger and Lavine, 2005; Lavine, 2001; Lavine et al, 2012; Yoo, 2010), on (2) data from Likert scale responses of two parties (Rudolph, 2011) or on (3) feeling thermometer scores of two different parties (Johnson, 2014; Leiter, 2019; Mutz, 2002). I follow the latter approach and make use of citizens’ evaluations of parties to capture ambivalence.…”
Section: Data and Operationalizationmentioning
confidence: 99%
“…The substantial similarity of the results obtained with the two alternative measures of ethnic diversity suggests that the effect is driven by the neighborhood concentration of immigrants from Asian and African countries, that is by ethnicities who are culturally and somatically more distant from Europeans and therefore more likely to be perceived as ethnic others by eligible voters. 15 Table 2 reports the partial effects of the percentage of African and Asian residents over the income distribution, using the estimation results of the model with the largest set of observable controls (last column of Table 1). Our main finding is the strongly heterogeneous effect of ethnic diversity on individual turnout for different levels of individual income.…”
Section: Pooled Ols Regressionsmentioning
confidence: 99%
“…3 Ambivalence has been found to have negative effects on political participation (see, for example, Mutz, 2002, andJohnson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified different types of ambivalence, including distinguishing between what has been described as objective ambivalence (measured by comparing people's answers to questions) and subjective or metapsychological ambivalence (explicitly asking people to state how ambivalent they are) (Craig et al, 2002;Holbrook and Krosnick, 2005;Lavine, 2001;Martinez et al, 2012). Ambivalence has been shown to be associated with more unstable attitudes and lower levels of political engagement (Alvarez and Brehm, 2002;Johnson, 2014). Rudolph and Popp (2007) argue that ambivalence is a function of the cognitive effort involved in forming political judgments.…”
Section: Introductionmentioning
confidence: 99%